CASE STUDY OF PRIMITIVE REFLEXES IMPACT ON SWIMMING SKILL ACQUISITION BY HEALTHY CHILDREN - Bogdanoviča, Irina; Lāriņš, Viesturs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Primitive reflexes is an automatic muscle reactions which are only present in the first few months, but can remain active in healthy children, thus, impacting on motor proficiency. There is little evidence how primitive reflexes influence on swimming skills acquisition by healthy children. The aim of the study is to examine how primitive reflexes influence swimming skills acquisition by healthy children. Subjects: two 7-year-old girls. Methods: Checklists by Oh et al., (2011) were used to evaluate swimming skill proficiency at swimming lesson 8 and 16. The results were represented as a percentage of the possible maximal score. The testing of the asymmetrical tonic neck reflex, the symmetrical tonic neck reflex, and the tonic labyrinthine reflex was done using Blythe’s, 5-point rating scale. The analysis was carried out using descriptive method. The first girl showed two reflexes at level 1, while the second girl demonstrated all tested reflexes at level 1, 2 and 3. The girl with less total score of reflexes (8%) achieved a better level of swimming proficiency (from 73% to 77%) than the girl with higher (25%) severity of these reflex (from 21% to 33%.). The obteined data evidence about influence of primitive reflexes on swimming skill acquisition by healthy children.